Promoting the Online Program of EfeX English Language Center Using a Promotional Video - Victoria Tanujaya; Jusuf Imam Ibrahim (Kata Kita: Journal of Language, Literature, and Teaching, 2023)
EfeX English Language Center recently launched EfeX Indonesia Maju (IM), a new online division. As it is in its early stages, EfeX IM has had limited enrollment due to a lack of promotional activities. To address this issue, I employed various theories, including Kalam's (2022) segmenting, targeting, and positioning theory, MasterClass' (2022) theory on product features, as well as Bhasin's (2021) and Leonard's (2022) theories on promotional videos. After identifying the target market as parents with elementary and middle-school students in major cities in Java, I conducted a questionnaire survey with 52 participants. The results revealed the need for a convenient, engaging, affordable online program that emphasizes speaking skills. To convey this message effectively, a promotional video will be created and shared on Instagram, serving as a versatile tool for promotion through WhatsApp, the website, and presentations.